Pengaruh Kualitas Layanan Dan Inovasi Produk Terhadap Loyalitas Konsumen Kopi Kenangan - Dia Ragasari; Adelia Riana Dewi (Soratekno Publisher, 2025)
Any business, even those in the beverage sector like Kopi Kenangan, can benefit greatly from having loyal customers. Retaining and growing market share requires an understanding of the elements that affect consumer loyalty. The purpose of this study is to investigate how customer loyalty at the Kopi Kenangan location in Yogyakarta is impacted by service quality and product innovation. 120 respondents who regularly visit the outlet participated in the survey used in this quantitative study. Google Forms was used to collect the data, and SPSS 25 was used for multiple linear regression analysis. The findings demonstrated that, at Kopi Kenangan, customer loyalty is significantly impacted by both service quality and product innovation, both partially and simultaneously. These results suggest that raising customer loyalty levels can be achieved by ongoing service quality improvement and product innovation. It follows that Kopi Kenangan must continue to be dedicated to upholding and enhancing the caliber of services offered. Additionally, it is recommended that the business continuously reinvent its products in order to draw in new clients and keep the loyalty of its current clientele. Kopi Kenangan can get a competitive edge and solidify its place in the market in this way.